ANALISIS POLA PEMBELIAN EMAS DENGAN ALGORITMA APRIORI: STRATEGI BUNDLING PRODUK UNTUK EOA GOLD BANDUNG - Aila Gema Safitri; Luthfi Faris; Taufik Rahmat Kurniawan; Ririn Suharsih (Journal of Innovation And Future Technology, 2025)
This research employs the Apriori algorithm to examine gold sales data at EOA Gold Bandung, with the objective of identifying association patterns in sales transactions that can enhance marketing strategies and optimise inventory management. The dataset employed comprises sales transactions from July 2023 to July 2024, encompassing purchase date, customer information, invoice number, and the type of gold purchased, with a weight ranging from 0.025 grams to 10 grams. The application of the Apriori algorithm with a minimum support value of 10% and a minimum confidence of 30% revealed a significant purchase pattern: namely, that 1-gram and 2-gram gold bars are often purchased together in a single transaction. The findings provide valuable insights for EOA Gold Bandung in designing a product bundling offering strategy, which can improve customer satisfaction, increase sales volume and enhance stock management efficiency. It is anticipated that the results of this analysis will contribute to the optimisation of data-driven business strategies in the gold sales sector.